Monopsony in Motion : Imperfect Competition in Labor Markets - Manning, Alan (Book collections on Project MUSE., 2003)
What happens if an employer cuts wages by one cent? Much of labour economics is built on the assumption that all the workers will quit immediately. In this text, Alan Manning mounts a systematic challenge to the standard model of perfect competition.